New memories - Rock'n'Roll Band; Forsman, Alf, 1952-; Lindholm, Dave, 1952-; Maijanen, Pave, 1950- ([Helsinki] : AllStar Music, 2005)
16 kappaletta.
Come 'round Betty -- I know what you want sister -- Hard grown boys -- You can do the jingle -- Rock 'n' roll water -- 88 dance halls -- Teenage nervous breakdown -- Mona -- Fever -- Rock 'n' roll fire -- Wooly bully -- California rag -- Rockin' pneumonia and the boogie woogie flu -- I'm gonna roll -- Hoochie coochie man -- Love me, come back home.
Rock 'n' Roll Band (yhtye): Lindholm, Dave (lauluääni, kitara). Maijanen, Pave (lauluääni, kitara, bassokitara). Forsman, Alf 'Affe' (rummut).
Puuttuu JYKin kokoelmasta
Keywords: konsertit; rock